The THE IMPROVEMENT OF READING COMPREHENSION IN ENGLISH THROUGH STUDENT TEAM ACHIEVEMENT DIVISION (STAD): READING COMPREHENSION IN ENGLISH THROUGH STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - Desy Chaniago; Depi Yunaspi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
The purpose of research is to improve the skills learners in understanding the reading text in English through STAD cooperative learning methods. The subjects were English learners at junior high school in Jakarta. Data collected at the initial observation as the first data, and then drafted two cycles are expected to be able to improve the skills of learners in understanding reading English text. The research model using action research model of Kurt Lewin, namely planning, action, observation and reflection. This action research was conducted over a six-month consisting of two observation meetings and eight meetings in two cycles. Four meetings, the first cycle and the second cycle of four meetings. Repairs carried out in every cycle and follow the post-test at the end of learning. Data were analyzed through qualitative and quantitative procedures. The study states that the ability of learners to understand the English text on the first cycle only 77.06. Then, the ability of learners rose to 82.55 in the second cycle. Based on that, the cooperative learning model of STAD very effective in improving the quality of the learning process and the ability of learners in understanding English texts.